A first-in-man phase i and pharmacokinetic study on CHR-2797 (Tosedostat), an inhibitor of M1 aminopeptidases, in patients with advanced solid tumors. - Reid, A; Protheroe, A; Attard, G; Hayward, N; Vidal, L; Spicer, J; Shaw, H; Bone, E; Carter, J; Hooftman, L; Harris, A; De Bono, J (2009)
PURPOSE: To determine the maximum tolerated dose, dose-limiting toxicity, pharmacokinetics, and preliminary therapeutic activity profile of CHR-2797 (tosedostat), a novel, orally bioavailable inhibitor of the M1 family of aminopeptidases with antiproliferative and antiangiogenic activity in vitro. EXPERIMENTAL DESIGN: A phase I study of accelerated titration design that escalated through nine doses (10-320 mg) in patients (Eastern Cooperative Oncology Group performance status, < or =2) with advanced solid tumors. CHR-2797 was administered once daily. RESULTS: Forty patients (median age, 60 years; range, 24-80 years; male, 27; female, 13) were treated in 12 cohorts with once daily doses (10-320 mg). Dose-limiting toxicities were thrombocytopenia, dizziness, and visual abnormalities in one patient, and anemia, blurred vision, and vomiting in a second patient at 320 mg, resulting in an inability to complete 28 days of study drug. The most commonly observed toxicities were fatigue, diarrhea, peripheral edema, nausea, dizziness, and constipation. One patient had a partial response (renal cell carcinoma) and four patients had stable disease for >6 months. CHR-2797 and its active metabolite, CHR-79888, show dose-proportional increases in plasma AUC and C(max). The terminal half-life for CHR-2797 is approximately 1 to 3.5 hours and between 6 and 11 hours for CHR-79888. Intracellular (packed blood cells) exposure to CHR-79888 is consistent with intracellular levels that proved to be efficacious in xenograft models. CONCLUSION: CHR-2797 is well tolerated and can be safely administered at doses that result in intracellular levels of CHR-79888 that are associated with activity in preclinical models. The recommended dose for single agent therapy in solid tumors is 240 mg/d.